Предмет: Алгебра,
автор: Kira9867
Помогите пожалуйста
Как делать??
(x-2)²+(4-x)×(x+3)
Ответы
Автор ответа:
0
формула сокр умножения (a±b)²=a²±ab+b²
(x-2)²+(4-x)×(x+3)=x²-4x+4+4x+12-x²-3x=-3x+16
(x-2)²+(4-x)×(x+3)=x²-4x+4+4x+12-x²-3x=-3x+16
Автор ответа:
0
раскрываем скобки
x^2-4x+4+4x+12-x^2-3x
сокращаем,остается:
4+12-3x=16-3x
x^2-4x+4+4x+12-x^2-3x
сокращаем,остается:
4+12-3x=16-3x
Похожие вопросы
Предмет: Русский язык,
автор: alievaminara821
Предмет: Музыка,
автор: Аноним
Предмет: Английский язык,
автор: ChelodoiMolovechik
Предмет: Математика,
автор: ЖэкаЗАЯЦ